2018
DOI: 10.12659/aot.907700
|View full text |Cite
|
Sign up to set email alerts
|

Nephrectomy Versus Embolization of Non-Functioning Renal Graft: A Systematic Review with a Proportional Meta-Analysis

Abstract: There is no standardization on the timing of the best approach to treat a non-functioning renal graft.We reviewed the literature and performed a proportional meta-analysis of case series of transplantectomy and embolization for a non-functioning renal graft. The groups were compared for mortality and morbidity outcomes.A total of 2421 patients were included in this review. Of these, 2232 patients underwent transplantectomy and 189 underwent percutaneous embolization. The mortality rate in the nephrectomy group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 38 publications
0
21
0
4
Order By: Relevance
“…Embolization is accomplished by the injection of ethanol followed by stainless steel coils into the branches of the renal artery 43 . Data on the efficacy and safety of this procedure compared with graft nephrectomy are limited, but a recent systematic review and meta‐analysis suggested that renal artery embolization may pose lower risks to patients with a failed allograft 44 . In this review, renal artery embolization successfully treated graft intolerance syndrome in the majority of cases, but 20% required follow‐up nephrectomy.…”
Section: Surgical Management Of a Failed Allograft: Risks Benefits And Impact On Hla Sensitizationmentioning
confidence: 99%
“…Embolization is accomplished by the injection of ethanol followed by stainless steel coils into the branches of the renal artery 43 . Data on the efficacy and safety of this procedure compared with graft nephrectomy are limited, but a recent systematic review and meta‐analysis suggested that renal artery embolization may pose lower risks to patients with a failed allograft 44 . In this review, renal artery embolization successfully treated graft intolerance syndrome in the majority of cases, but 20% required follow‐up nephrectomy.…”
Section: Surgical Management Of a Failed Allograft: Risks Benefits And Impact On Hla Sensitizationmentioning
confidence: 99%
“…Trans‐vascular embolization demonstrated significantly less postoperative haemorrhages and infections compared with open allograft nephrectomy. Furthermore, the all‐cause mortality was 0.1% in the embolization cohort with 9 case series including 189 patients compared to 4% in conventional transplantectomy cohort in 17 case series including 2175 patients [42].…”
Section: Discussionmentioning
confidence: 99%
“…A common indication for the elimination of the effects of the graft is the control of graft intolerance syndrome through embolization and restart immunosuppression treatment, as was the case in our patient. The most frequent complication after this procedure is post-embolization syndrome, with an incidence of 68%, characterized by fever lasting 2 to 5 days in 59% of cases, local pain, hematuria, nausea and vomiting, which, if persisting, requires the presence of vascularization of the graft and the persistence of immune intolerance to be ruled out [6].…”
Section: Discussionmentioning
confidence: 99%